Chronicling the land rights movement: the democratic role of Australian Indigenous land rights publications. Issue 1 (August 2016) - Burrows, Elizabeth
The Australian land rights debate has polarized public opinion since the 1960s. Deliberative democratic theory argues that sound public opinion forms after citizens engage in discussions about issues of concern, including mediated conversations. Yet, mainstream media coverage of native title disputes has often excluded and ridiculed Indigenous stakeholders. This study draws on in-depth interview and archival data and newspaper content analysis, to examine how land rights publications produced since 1971 have injected Indigenous voices and perspectives into mediated public debates. Producers of land rights publications have sought to redress the balance in democratic processes by providing access to authentic, Indigenous voices. Their content has influenced political policy and public opinion and challenged inaccuracies and misrepresentations within mainstream media coverage.